A method for the quantification of 8-methoxypsoralen by mass spectrometry for offline extracorporeal photopheresis. Issue 2 (15th December 2016) - Hähnel, Viola; Dormann, Frauke; Nitsopoulos, Athanasios; Friedle, Albrecht; Ahrens, Norbert
Abstract : An LC-MS/MS assay for analysis of 8-methoxypsoralene was developed as assay to monitor extracorporeal photopheresis. This allows quantification of 8-MOP adhering to plastic surface and of the UV light-dependent decay constant. Abstract : Background : Extracorporeal photopheresis (ECP) is an efficient method to treat various autoimmune diseases, cutaneous T-cell lymphoma, and graft- versus -host disease. It is based on the ex vivo inactivation of lymphocytes by 8-methoxypsoralen (8-MOP)/UV light treatment. Despite the adhesive, lipophilic nature of 8-MOP, no quality control is established for the ECP procedure. Methods : We developed a sensitive high-performance liquid chromatography/tandem mass spectrometry (HPLC-MS/MS) assay to monitor residual 8-MOP concentration after UVA irradiation in the whole blood supernatant after acetonitrile precipitation. Results : The preanalytical stability of 8-MOP exceeded 7 days, allowing batch mode analysis. Linearity was determined with R 2 above 0.99. The 8-MOP concentrations decreased exponentially after UV exposure, with decay constants of 0.0259 in plasma and 0.0528 in saline. The recovery of 8-MOP in photopheresates was about 68%, indicating binding to DNA as well as to plastic structures. UVA induced no 8-MOP fragmentation, but caused self-adducts under extreme conditions (10-fold UV dosage). Conclusions : Detection of 8-MOP proved to be feasible and demonstrated that the doses were in the pharmaceutically active range.